Homoeopathic Medical Education: Need for Uniformity and Harmonization (Homoeopathy for All, 2022)
Homoeopathy is considered the second  most popular and frequently used form  of Traditional and Complementary  Medicine (T&CM), according to  World Health Organization (WHO).  It is widely used in all WHO regions  with a presence in about 100 countries  worldwide. With legal recognition  as an individual system of medicine  in 42 countries, it is recognized as a  part of complementary and alternative  medicine in 28 countries.1
Keywords: Traditional and Complementary; 28 countries; EDUCATION